On real investment by new ventures - Reinhard Schulte (Leuphana Universität Lüneburg, Lehrstuhl Gründungsmanagement, 2015)
This paper contributes to the literature on new firms in two ways. First, by addressing new venture investment, it focuses on a largely neglected, but important, issue of new firm business decisions. Second, it provides a valuable picture for how real investing by new businesses is going to evolve over time. Results suggest that investments by new firms are prone to an s-shaped time pattern rather than a random, linear or a gradually growing trajectory, or a capital market driven behavior as is assumed usually in the literature on investment decisions. By constructing a framework for future research on new venture investment, this article suggests specific research opportunities for future contributions to this body of knowledge. Based on the developed theorem, four main strands for future research can be identified, namely, (1) the empirical validation of the theorem per se, including trajectory, duration, and level of investment; (2) the link between investment and funding of the venture; (3) the link between investment and new venture development; and (4) investment as an adjustment of aggregate capital stock.
urn:nbn:de:101:1-20160218984
Keywords: D92; L25; M13; M21; 330; new ventures; start up; investment; investment dynamics; investment patterns